Zamolodchikov Tetrahedral Equation and Higher Hamiltonians of 2d Quantum Integrable Systems - Talalaev, D.V. (Symmetry, Integrability and Geometry: Methods and Applications, 2017)
The main aim of this work is to develop a method of constructing higher Hamiltonians of quantum integrable systems associated with the solution of the Zamolodchikov tetrahedral equation. As opposed to the result of V.V. Bazhanov and S.M. Sergeev the approach presented here is effective for generic solutions of the tetrahedral equation without spectral parameter. In a sense, this result is a two-dimensional generalization of the method by J.-M. Maillet. The work is a part of the project relating the tetrahedral equation with the quasi-invariants of 2-knots.